Sol-Gel Synthesis of Nickel-Doped Aluminium Oxide - Ali, A.F. (Asian Journal of Chemistry, 2010)
Almost single-phase 8% Ni-doped alumina compositions were derived, by the sol-gel method, from both organic and aqueous media. Thermal analysis, XRD, and FT-IR showed that the use of metal organic precursors, and working in an almost fully organic medium, is more advantageous. In these conditions, Ni-doped gamma-alumilla could be obtained at a relatively lower temperature, 500°C, than in case of working in an aqueous medium where a delta-alumina phase was formed at temperatures not lower than 600°C. The method of preparation did not alter the desired metal ratio as checked by atomic absorption spectroscopy.